Interpreting traumatic narratives of unaccompanied child migrants in the United States: Effects, challenges and strategies - Sultanic, Indira (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This research examines the challenges of interpreting for unaccompanied child migrants in the United States and the effect of exposure to the traumatic narratives told by these children, as experienced by the interpreters involved. When a traumatic narrative is introduced, over time it has an effect on the emotional and psychological well-being of an interpreter. This study therefore focuses on the coping mechanisms interpreters employ to minimize the effects of long-term exposure to the traumatic content when they work in settings involving migrant children. During the past few decades, a number of studies have been conducted on the emotional and psychological effects of traumatic content on interpreters who work in various contexts, but very few have focused on interactions involving this vulnerable group of migrants. This study uses a qualitative approach in which data were collected through semi-structured interviews with both trained and ad hoc interpreters who work or have worked with unaccompanied children seeking asylum in the United States since the summer of 2014. The study contributes to the growing body of literature on public service interpreting. It does so by offering the interpreter’s perspective on the specific challenges and difficulties of interpreting for unaccompanied child migrants in that country who face near-insurmountable systemic barriers and challenges. It sheds light on the delicate nature of interpreting for vulnerable groups, especially children, who are seeking asylum there. Furthermore, it brings into focus the applicable strategies that help interpreters prepare for interpreting traumatic experiences, and also for coping both during the act of interpreting and afterwards.